Comparative Analysis of Food Security Status of Farming Households in the Coastal and the Forest Communities of Central Region of Ghana - Kuwornu, John K.M; Suleyman, Demi M; Amegashie, Ditchfield P.K. (Asian Journal of Empirical Research, 2013)
The study examines the food security status of farming households in the Coastal and forest belts of the Central region of Ghana. A multistage sampling technique was used to select the households that were interviewed using a structured questionnaire. In all, data obtained 260 households were used for the analysis (120 and 140 households from the forest and Coastal communities, respectively). The study revealed that majority of the households (67.9%) was food insecure. In this respect, farming households in the forest areas were less food insecure compared to their counterpart in the coastal areas. Thus, food insecure farming households in the coastal areas consume far lower (34%) than their recommended daily calorie intake than food insecure households in the forest areas (26%). Food crop farmers are the most affected in terms of food insecurity compared to the other groups of farmers (Tree crops and Vegetable farmers). The food security status of the farming households across both coastal and forest communities are influenced by dependency ratio, and quantity of own farm production. Furthermore, access to credit, and total annual income improved food security status of farming households in the forest communities but not relevant to coastal communities. Higher education improves food security status of farming households in the coastal communities but not significant among farming households in the forest communities. These results have policy implications for improving food security situation in developing countries.